2021
DOI: 10.3390/ijms22094469
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle–Adipose Tissue–Tumor Axis: Molecular Mechanisms Linking Exercise Training in Prostate Cancer

Abstract: Increased visceral adiposity may influence the development of prostate cancer (PCa) aggressive tumors and cancer mortality. White adipose tissue (WAT), usually referred to as periprostatic adipose tissue (PPAT), surrounds the prostatic gland and has emerged as a potential mediator of the tumor microenvironment. Exercise training (ET) induces several adaptations in both skeletal muscle and WAT. Some of these effects are mediated by ET-induced synthesis and secretion of several proteins, known as myo- and adipok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 189 publications
(296 reference statements)
0
2
0
Order By: Relevance
“…Rocha-Rodrigues et al proposed that exercise training reduces visceral fat volume, increases skeletal muscle mass in patients with PCa, and improves the tumor microenvironment. Exercise training influences PCa progression by modulating the secretion of adipokines from PPAT and other adipose tissues and the secretion of myokines from skeletal muscles 80 . In addition, the participation of patients with PCa in exercise training after diagnosis may improve their survival 81 .…”
Section: Some Elements That Indirectly (Through Ppat) or Directly Aff...mentioning
confidence: 99%
“…Rocha-Rodrigues et al proposed that exercise training reduces visceral fat volume, increases skeletal muscle mass in patients with PCa, and improves the tumor microenvironment. Exercise training influences PCa progression by modulating the secretion of adipokines from PPAT and other adipose tissues and the secretion of myokines from skeletal muscles 80 . In addition, the participation of patients with PCa in exercise training after diagnosis may improve their survival 81 .…”
Section: Some Elements That Indirectly (Through Ppat) or Directly Aff...mentioning
confidence: 99%
“…Recently, with the emergence of omics-based strategies, new exercise-induced myokines are gradually being identified in the muscle secretome [ 202 206 ]. Although the evidence, that exercise-driven myokines may play a role in cancer prevention or therapy, is still limited, several preclinical studies have indicated muscle-derived Oncostatin M (OSM) and Irisin may be effective against prostate and breast cancer [ 183 , 207 210 ]. In addition, the myokine secreted protein acidic and rich in cysteine (SPARC) produced by exercise training has been identified as an anticancer factor, as evidenced by decreased tumorigenesis in trained mice bearing colon cancer [ 211 213 ].…”
Section: The Interplay Between Activity–rest Cycles and Cancermentioning
confidence: 99%
“…It is imperative that the impact of lifestyle and long-term health outcomes continue to be studied and results disseminated to the public. The role of PA in protection from cancer has continued to receive considerable attention with new insight into the molecular mechanisms, and research on the signalling effects of adipokines and myokines becoming more prominent ( 6 ). However, despite unhealthy lifestyle choices generally being well known to increase risk of cancer, there is not a full and consistent understanding of this across society and knowledge of how this may translate into daily sensible choices is not so well developed ( 7 ).…”
Section: Introductionmentioning
confidence: 99%